The legacy of Sir Reginald Stephen Garfield Todd in Zimbabwean public life history - Masengwe, Gift (HTS teologiese studies, 2021)
This article investigates the contribution of white liberal politics of an ex-missionary New Zealander, Sir Reginald Stephen Garfield Todd (from 1953 to 1958), on the development of Southern Rhodesia towards becoming an independent state. It outlines the contribution he made towards the progress of black Zimbabweans in a number of spheres. It arouses interest in contemporary Zimbabwean religious and political discourses. Todd held a hybridity of roles in transitional politics from the blunting settler racism to the sharpening of African capability on multi-racial democracy important for our debate on the decolonisation of southern Africa. He was a rhetorically gifted radical paternalist who adopted reformist policies to advance both the African cause and his prophetic vocation. He suggested technocratic solutions that could reorganise and diversify political and economic options.Contribution: This study uses critical discourse analysis (CDA) on the wider literature on Todd’s biography and African policies in view of his Christian vocation towards changing conditions of socio-economic, political-religious and technological-technocratic solutions to contemporary African independence. He was a man of his times living and working in an increasingly problematic context guided by the Christian principles in which he was reared. He is the ‘father of faith’ in the Church of Christ in Zimbabwe (COCZ), and leaves us pedagogical lessons on human security, gender equality, church governance and human well-being that require review within the contemporary Christian fraternity.